Role of Dexmedetomidine as synergistic agent to prolong subarchnoid block duration - Jawad Hameed; Shakeel Ahmed; Maqsood Ahmed Siddiqui; Amjad Nadeem; Aslam Pervaiz; Syed Ali Abbas Rahat (Medical Journal of South Punjab, 2024)
Objective: to evaluate the impact of dexmedetomidine when administered intravenously in infusion or bolus on subarachnoid anesthesia in combination with hyperbaric bupivacaine. Methodology: A randomized controlled trial was conducted at the department of Anesthesia, Lady Reading Hospital Peshawar, Pakistan, from January 2023 to June 2023. T10 level was pointed for assessment of snsory blockade, and periodically motor blockade was assessed until the achievement of modified Bromage score 3. Sedation levels were assessed using the Ramsay score, while adverse effects such as nausea, bradycardia and hypotension, vomiting, diarrhea, and pruritus were closely monitored and documented throughout the study period. Results: The onset time of sensory blockade was significantly higher in Group Dex+B compared to Group B (p < 0.001). Additionally, the duration of sensory blockade was also significantly higher in Group Dex+B than in Group B (p < 0.001). Moreover, the rate of recovery of complete sensory block was notably higher in Group Dex+B compared to Group B (p < 0.001). Similarly, when considering motor blockade, both the onset and recovery were significantly faster in Group Dex+B than in Group B (p < 0.001) Conclusion: The findings from our study indicate that when administered intravenously, dexmedetomidine, whether given as a bolus or through continuous infusion, leads to a significant extension in sensory and motor blockade duration.